A laptop per child in rural schools of Peru: an analysis of barriers and facilitators - Carlos David Laura Quispe (2019)
This study aims to identify barriers and facilitators that arise from the introduction of the XO- laptop-computer-designed for children - in rural schools in Peru. The investigation started by presenting a conceptual framework from a review of theoretical work, along with a review of international experience including a description of the Hone laptop per child program” (0LPC by its initials in English). The data analysis included the categorization of information collected and triangulation with other sources of information. The study concludes with a discussion of a range of factors that facilitate and hinder the integration of the laptop into the school curriculum.